Targeting Thyroid Hormone/Thyroid Hormone Receptor Axis: An Attractive Therapy Strategy in Liver Diseases - Tang, Qianyu; Zeng, Min; Chen, Linxi; Fu, Nian (Frontiers in Pharmacology, 2022)
Thyroid hormone/thyroid hormone receptor (TH/TR) axis is characterized by TH with the assistance of plasma membrane transporters to combine with TR and mediate biological activities. Growing evidence suggests that TH/TR participates in plenty of hepatic metabolism. Thus, this review focuses on the role of the TH/TR axis in the liver diseases. To be specific, the TH/TR axis may improve metabolic-associated fatty liver disease, hepatitis, liver fibrosis, and liver injury while exacerbating the progression of acute liver failure and alcoholic liver disease. Also, the TH/TR axis has paradoxical roles in hepatocellular carcinoma. The TH/TR axis may be a prospecting target to cure hepatic diseases.